PENGARUH BUDAYA ORGANSIASI, MOTIVASI DAN KEDISIPLINAN TERHADAP KINERJA DOSEN - Jose Beno (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2014)
Purpose of this study to analyze how the influence of organizational culture, motivation and discipline to the performance Sailing Science Lecturer at the Polytechnic of Semarang?